2011
DOI: 10.1111/j.1476-5381.2011.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists show GTP‐sensitive high‐affinity binding to the sigma‐1 receptor

Abstract: BACKGROUND AND PURPOSESigma-1 receptors are atypical receptors with potentially two transmembrane domains. Antagonists require doses significantly higher than their published affinities to have biological effects. We have reassessed the binding characteristics of these ligands and found antagonists bind to high-and low-affinity states not distinguished by agonists. EXPERIMENTAL APPROACHThe affinities of sigma-1 receptor ligands was assessed using radioligand saturation and competition binding of [ 3 H]-(+)-pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…This discrepancy between the measured affinity and in vitro potency values is consistent with the reports of others who have observed the same phenomena for other S1R ligands that facilitate BDNF secretion (Fujimoto et al, 2012; Malik et al, 2015), or other S1R drugs that produce other S1R-mediated functional outputs such as neurite sprouting or changes in intracellular calcium (Brimson et al, 2011; Ishima et al, 2014; Ishima and Hashimoto, 2012; Ishima et al, 2008; Nishimura et al, 2008; Wu and Bowen, 2008). Though reason for the discrepancy between the affinity and potency is not entirely clear, the findings of this study nevertheless provide new insight into the structure-activity relationship and functional selectivity of haloperidol metabolites at the S1R.…”
Section: Discussionsupporting
confidence: 90%
“…This discrepancy between the measured affinity and in vitro potency values is consistent with the reports of others who have observed the same phenomena for other S1R ligands that facilitate BDNF secretion (Fujimoto et al, 2012; Malik et al, 2015), or other S1R drugs that produce other S1R-mediated functional outputs such as neurite sprouting or changes in intracellular calcium (Brimson et al, 2011; Ishima et al, 2014; Ishima and Hashimoto, 2012; Ishima et al, 2008; Nishimura et al, 2008; Wu and Bowen, 2008). Though reason for the discrepancy between the affinity and potency is not entirely clear, the findings of this study nevertheless provide new insight into the structure-activity relationship and functional selectivity of haloperidol metabolites at the S1R.…”
Section: Discussionsupporting
confidence: 90%
“…Treatment with some Sigma1 ligands has been shown to modulate cytosolic calcium levels (Brent et al, 1996;Hayashi and Su, 2007). Recent evidence (Brimson et al, 2011) demonstrates that IPAG-induced intracellular calcium release occurs at concentrations that clearly exceed the UPR and autophagy activating concentrations presented herein (Figs. 1, 3, and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, results reported in [10] showed that competitive displacement of labeled III in vitro corresponded to different receptor binding models depending on the presence of GTP in the medium. Given the previously demonstrated significant differences between C57B1/6, BALB/c, and CD-1 mice in responses to handling [11], it remains possible that endogenous modulators have different effects on Sigmar1 in inbred strains during manipulation.…”
Section: Discussionmentioning
confidence: 77%